Capacity building through comprehensive implementation research training and mentorship: an approach for translating knowledge into practice - Asampong, E.; Kamau, E.M; Tabong, P.T.; et al. (Springer Nature, 2023)
Abstract Background Implementation research (IR) is increasingly gaining popularity as the act of carrying an intention into effect. It is thus an important approach to addressing individual practices, policies, programmes and other technologies to solving public health problems. Low- and middle-income countries (LMICs) continue to experience public health problems which could be addressed using implementation research. These countries however fall behind prioritizing implementation research due to the disorganized approach used to providing knowledge about the value and scope of implementation research. This paper seeks to explain steps taken to resolve this by capacity strengthening activities through a comprehensive implementation research training and mentorship programme which was informed by needs assessment. Methods The roll-out of the comprehensive implementation research training and mentorship was done in phases, including engaging the implementation research community through TDR Global, competency building for programme officers and ethical review board/committee members, and practical guidance to develop an implementation research proposal. The Bloom taxonomy guided the training whilst the Kirkpatrick Model was used for the evaluation of the effectiveness of the capacity building. Results The findings identified critical areas of mentors and how mentorship should be structured and the most effective ways of delivering mentorship. These findings were used to develop a mentorship guide in IR. The mentorship guidance is to be used as a check-tool for mentoring participants during trainings as part of the package of resources in implementation research. It is also to be used in equipping review board members with knowledge on ethical issues in implementation research. Conclusion The approach for providing comprehensive implementation research training and mentorship for programme personnel has provided an opportunity for both potential mentors and mentees to make inputs
Research Article
Keywords: Implementation Research; public health; Kirkpatrick Model; mentorship